Pengelolaan hutan jati pada masa pemerintahan kolonial Hindia-Belanda di Ngandjoek Tahun 1927-1942 - Shinta Ayu Mutiara Sari; Dewa Agung Gede Agung (Historiography: Journal of Indonesian History and Education, 2023)
Teak wood is a product of forced cultivation which is suitable for growing on soils containing lime. Teak wood grows a lot in Central Java and East Java because it has lime-containing soil making it suitable for growing teak wood. In 1903 there was a teak crisis so the Dutch East Indies colonial government prepared several policies to save the teak forests. So that led to several new policies to save teak forests. This study shows the management of teak forests in Ngandjoek by the Dutch East Indies colonial government. The management of teak wood forests is very interesting to study, both in terms of management and the policies made by the Dutch East Indies colonial government. The purpose of this writing is to narrate the results of forest management in Ngandjoek. The research uses the historical method which has five stages including topic selection, heuristics, source criticism, interpretation and historiography. The results of this paper show the management of teak wood forests in Ngandjoek in 1927.Kayu jati merupakan salah satu produk dari tanam paksa yang cocok tumbuh di tanah yang menggandung kapur. Kayu jati banyak tumbuh di Jawa Tengah dan Jawa Timur karena memiliki tanah yang mengandung kapur sehingga cocok untuk ditumbuhi kayu jati. Pada tahun 1903 terjadi krisis kayu jati sehingga pemerintah kolonial Hindia Belanda menyiapkan beberapa kebijakan untuk menyelamatkan hutan kayu jati. Sehingga memunculkan beberapa kebijakan baru untuk menyelamatkan hutan kayu jati. Studi ini menunjukkan pengelolaan hutan kayu jati di Ngandjoek oleh pemerintah kolonial Hindia Belanda. Pengelolaan hutan kayu jati sangat menarik untuk di kaji, baik dari pengelolaannya maupun kebijakan yang di buat oleh pemerintah kolonial Hindia Belanda. Tujuan penulisan ini untuk mengetahui hasil pengelolaan hutan di Ngandjoek. Penelitian menggunakan metode sejarah yang memiliki lima tahapan diantaranya pemilihan topik, heuristik, kritik sumber, interpretasi dan historiografi. Hasil dari penulisan ini menunjukkan pengelolaan hutan kayu jati di Ngandjoek tahun 1927.Â